2015
DOI: 10.1007/s12028-015-0146-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cerebrovascular Autoregulation Using Regional Cerebral Blood Flow in Surgically Managed Brain Trauma Patients

Abstract: Assessment of autoregulation with Hemedex® rCBF monitor is feasible and could be used to guide CPP management strategies to optimize both autoregulation and perfusion. Autoregulatory impairment and CPPopt vary considerably between patients, and the addition of rCBF monitoring could help guide CPP targeting decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…Autoregulation function during cerebral ischemia is the main physiological activity to maintain normal brain metabolism. Loss of autoregulation could result in disruption of brain metabolism, induction of brain edema, and increase the severity ( 25 ), which were consistent with our results on abnormal pial artery dilation, increasing cell apoptosis and severe motor function injury. The previous study has shown that salvinorin A treatment exerted vessel dilation function in normal brain tissue ( 9 ).…”
Section: Discussionsupporting
confidence: 91%
“…Autoregulation function during cerebral ischemia is the main physiological activity to maintain normal brain metabolism. Loss of autoregulation could result in disruption of brain metabolism, induction of brain edema, and increase the severity ( 25 ), which were consistent with our results on abnormal pial artery dilation, increasing cell apoptosis and severe motor function injury. The previous study has shown that salvinorin A treatment exerted vessel dilation function in normal brain tissue ( 9 ).…”
Section: Discussionsupporting
confidence: 91%
“…Of the 25 articles included in this review, 17 are formal publications [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and 8 are meeting abstracts. 18,[28][29][30][31][32][33] Of these articles, 23 have a prospective 10,11, and 2 have a retrospective observational design.…”
Section: Study Description and Demographicsmentioning
confidence: 99%
“…The type of thermal diffusion device used was parenchymal in 16 studies [11][12][13][16][17][18][19][20]23,24,26,[30][31][32][33][34] and cortical for the remaining 9 studies. 10,14,15,21,22,25,[27][28][29] CBF measurements are reported in terms of mL/100 g/min.…”
Section: Thermal Diffusion Flowmetry Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…2), allowing the effects of different therapies on the autoregulatory state to be assessed. Similar autoregulation indices between CPP and PbtO 2 27 and CPP and CBF 58 have been constructed, although they have not been validated to the same degree as PRx.…”
Section: Figmentioning
confidence: 99%